CONFESSIONAL MNOGOZVUCHIE IN SOCIO-CULTURAL EDUCATIONAL SPACE - L. Filindash (Вестник университета)
The article deals with the problem of social interaction of students in a multi-religious and multi-ethnic educational space. Identity, the formation of "self-concept", social activity, the intercultural communication on personal, interpersonal, group, and intergroup levels is characterized, in particular, religious marker, which manifests itself in a stable moral foundations, moral values, adherence to tradition.